The history, current state and future of electronic chemistry learning environments - Johannes Pernaa; Maija Aksela (LUMAT, 2013)
This article discusses the historical development, current state, and needs future development of electronic learning environments for chemistry education. The study is by nature a theoretical literature review. Its aim is to canvass how the requirements related to chemistry learning environments have changed over time. By understanding the history, the further needs for development can be supported in the fast-advancing field of technology. The objects of investigation are the changes in both technology and chemistry education. Theory of blended learning was used as the theoretical framework for the study. In the theory section, it is combined with the possibilities of ICT in chemistry teaching and learning. In the historical framework of the article, the change in the requirements and possibilities of ICT-based chemistry learning environments is discussed from the perspective the recent history of chemistry education. It has been divided into three periods: 1) The use of ICT before the year 1999, 2) The use between the years 2000 and 2010, and 3) The use in 2011 and later. For each of the periods, the possibilities in chemistry education of one significant ICT tool are presented. In the analysis section of the study, these examples are reflected on the theory of blended chemistry learning and technological development. At the end of the article, three instructions are presented that can be employed in the use and development of chemistry learning environments. The instructions support the development of chemistry learning environment solutions that are technologically durable and take advantage of the various possibilities of ICT.